SÓLO DIOS BASTA - Berthold Anton Pareira (Litbang STFT Widya Sasana Malang, 2015)
The great Carmelite mystic, St.Teresa of Jesus, in her didactic and devotional poem titled Eficacia De La Paciencia or Efficacy of Patience gives this advice in the opening line “Let nothing trouble you” and concludes with this saying, “God alone suffices”. Who in this life can say this and when? What does it mean? What does it mean in practical life? What should we do? I try to answer these questions in the light of Scripture,the Book of Life.